Analysis of Language Politeness in The Drama of Al-Khātam by 'Ali Aḥmad Bākaṡīr (A Pragmatic Study) - Refanzah, Wahid; Yoyo, Yoyo (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2023)
This research aims to determine politeness in Arabic sentences in the drama al-Khatām by Ali Ahmad Bākasīr using politeness theory according to Brown and Levinson. Using Brown and Levinson's politeness theory, Arabic politeness can be identified in al-Khatām's drama text. Details of the politeness of the language used can be seen when analyzing and observing the language in this drama, such as differences in social strata and life conflicts influencing the politeness of the language used between the speaker and hearer (H). This research is a type of qualitative descriptive research with a pragmatic approach. The data collection technique used was sorting and recording. The results of the study found positive politeness strategies used by the characters in this drama to maintain the cheerful face of the interlocutor in the form of paying attention to interests, desires, needs (not paying attention to H's interests, actions, goods, and desires), exaggerating interest, approval, support, and sympathy. (exaggerating interest, approval, sympathy for H), giving compassion to the interlocutor (showing empathy to H), seeking approval, and being optimistic (be optimistic). Negative strategies to maintain the speaker's negative face include pessimism, giving respect, and nominalization. Characters also do not perform speech acts or speak silently to prevent facial threats from appearing. Face-threatening actions are also found in the dialogue between characters in the drama al-Khatām, both threats to positive faces and threats to negative faces.